Non parabolicity effects on electron-confined lo-phonon scattering rates in Ga As - Al0.45 Ga0.55 As superlattice - Abouelaoualim, D. (Journal of Research (Science), 2025)
We investigate theoretically the effect on non-parabolic band structure on the electron-confined LO-phonon scattering rate in GaAS-Al0.45Ga0.55As superlattice using the quantum treatment, the new wave function of electron miniband conduction of superlattice and a reformulation slab model for the confined LO-phonon modes. An expression for the scattering rates is obtained. Our results show that for transitions due to the emission of confined LO-phonon the scattering rates significantly increase for non-parabolicity case.